Differential regulation of neurexin at glutamatergic and GABAergic synapses - Pregno, Giulia; Frola, Elena; Graziano, Stefania; Patrizi, Annarita; Bussolino, Federico; Arese, Marco; Sassoè-Pognetto, Marco (Frontiers in Cellular Neuroscience, 2013)
Neurexins (Nrxs) have emerged as potential determinants of synaptic specificity, but little is known about their localization at central synapses. Here we show that Nrxs have a remarkably selective localization at distinct types of glutamatergic synapses and we reveal an unexpected ontogenetic regulation of Nrx expression at GABAergic synapses. Our data indicate that synapses are specified by molecular interactions that involve both Nrx-dependent and Nrx-independent mechanisms. We propose that differences in the spatio-temporal profile of Nrx expression may contribute to specify the molecular identity of synapses.